Support where it’s needed: Helping language professionals to develop online teaching skills for the 21st century - Stanojević, Mateusz-Milan; Ernest, Pauline; Emke, Martina; Germain-Rutheford, Aline; Hampel, Regine; Hopkins, Joseph; Stickler, Ursula (2012)
In this paper we present the rationale behind the Developing Online Teachings Skills (DOTS) targeted support activity and an outline of the workshop. We believe that online teaching skills are essential in the 21st century language classroom, but they need to be based on an approach where language learning pedagogy is supported by technology. We argue that the best way to achieve this is through socio-cultural and constructivist theories of learning, which naturally translates into using a blended approach to our workshops, where the online element is presented through the DOTS workspace constructed on the Moodle platform.
ENG